Sosialisasi Cassamee Berbasis Singkong sebagai Upaya Mengurangi Ketergantungan Beras dan Menguatkan Pangan Lokal di Kampung Ciwulung: Socialization of Cassava Based Cassamee as an Effort to Reduce Rice Dependency and Strengthen Local Food in Ciwulung Village - Rahma Rizqia; Fathiyah Salsabilah; Sarifah Sarifah; Naya Akhwatul Janna; Aef Saefulloh; Arta Firdauli Doloksaribu; Rida Oktorida Khastini (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Indonesia has great agricultural potential, but the community's dependence on one main food source, namely rice, is still high, posing a risk to food security, especially in rural areas. Cassava, as an abundant local food source, has not been optimally utilized and has low economic value. This activity was carried out to identify the potential of cassava and introduce Cassamee as an alternative cassava-based food innovation to encourage food diversification and strengthen food security in Kemanisan Village, Tirtayasa District, Serang Regency. The activity was carried out through an educational and training approach that included food security socialization, screening of cassava-processing demonstration videos, introduction of Cassamee products, and product-tasting sessions. Data collection was conducted with 28 respondents using pre- and post-activity test instruments to measure knowledge, and questionnaires to assess attitudes and food consumption behavior. The data were analyzed descriptively and quantitatively using mean values and percentages. The activity results showed an increase in community knowledge after dissemination. In addition, the community's attitude toward and acceptance of Cassamee were positive. Overall, this activity increased the community's understanding and awareness of the importance of food diversification based on local resources, thereby potentially supporting food security and economic independence in rural communities.